The Experiences of Professional Moroccan Women in the Canadian Job Market - Kaddouri, Kaoutar (Université d'Ottawa / University of Ottawa, 2011)
In Canada, the non-recognition of foreign credentials remains a considerable policy issue as well as a challenge for skilled immigrants. Many studies have shed light on the difficulties that foreign professionals face when seeking a placement in the Canadian job market. This thesis focused on the experiences of professional women from Morocco on the basis of the premise that every racialized group’s immigration experience deserves a space in the literature to voice their realities and inspire policy considerations. As a result, this study focused on examining the experiences of Moroccan women in the Canadian job market and the impact thereof, on their socio-economic status, and as such, health and well-being. In order to effectively capture the experiences of this particular community, a fieldwork study was conducted in the form of semi-structured individual interviews with twelve women who immigrated to Canada from Morocco with professional qualifications. Based on the participants’ accounts, I described that systemic discrimination as manifested in Othering and racialization remain major obstacles to the realization of equal access in the Canadian labour market. All in all, this research provides valuable insight into the plight of skilled immigrants in Canada and thus, offers strong policy recommendations to facilitate a more effective integration process for this group into the Canadian Job market.
Keywords: Non-recognition of Foreign Credentials; Brain Drain; Quebec; Moroccan Women; Skilled Immigration; Labour Market